Some Methodological Issues of Scientific Geosophy - Yu. O. Kyselov (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 8, 2023)
Our time is characterized by a dialectical combination of opposite processes in the development of science - differentiation, expressed in the emergence of new analytical, sectoral disciplines, and integration, which consists in the design of synthetic, complex disciplines mainly at the frontiers of science. One of the youngest synthetic geographic disciplines is geosophy, which was established about a hundred years ago at the boundary of geography and philosophy. In fact, elements of geosophy were present in the works created by ancient Greek and Roman scholars and philosophers, but in the new time the first who used the term “geosophy”, was German geographer Ewald Banse. But his geosophy occupied a place between the science and art; the modern, hardly scientific, geosophy was created by American scholar John Kirtland Wright. So, for more than hundred years, this scientific discipline has passed a difficult way of development, due to both internal, expressed in the nature of the discipline itself, and external (ideological, geopolitical, etc.) factors. The object of geosophy is human space, that is, space perceived and conceived by man. Nowadays, post-non-classical methodological approaches are becoming more widely used in geosophy - besides geosophical, it is noospheric (created by Pierre Teillard de Chardin and Volodymyr Vernadskyi), synergistic (established by Isabelle Stengers and Ilya Prigogine), eco-evolutionary (known also as the conception of sustainable development initiated by Dennis Meadows) and passionate (discovered by Lev Gumilyov). They are based on a fundamentally new relationship between the subject and the object, qualitatively different from what has traditionally been recognized as classical and non-classical geography. One feature of post-non-classical approaches is subject-object convergence. In particular, the content of the geosophical approach is to consider geographical features as totals that represent the integrated unity of the all natural and human components. Possibilities of its application exist in almost all sections of geography. One of the main ones in all geography is the category of landscape. The ambiguity of its interpretation attests to the fundamental importance of this concept, its exceptional role in the knowledge of the earth’s surface as a multidimensional reality. In particular, the geosophical point of view on landscape consists in the conception of the landscape and ethnicity interaction. From the diversity of landscape understandings, two basic concepts stand out. The content of one of them, dating back to the 19th century, is to see the landscape as a general picture of the terrain, which was interpreted as totality. From other positions, designed in the early twentieth century, the landscape is understood as a real existing natural material object, characterized by genetic homogeneity, the presence of vertical and horizontal structure and clearly defined boundaries. The coexistence of the aforementioned landscape concepts and the search for possibilities of combining them is one of the important theoretical issues of modern geography, in particular, geosophy. It is stressed that the categories of “spirit”, “consciousness”, “information field’ shaping a triad, integrate spiritual and material, ideal and real, subjective and objective components of landscape in a whole unity.